Plant proteomics - Finnie, C.
The proteome comprises all protein species resulting from gene expression in a cell,organelle, tissue or organism. By definition, proteomics aims to identify and characterize the expression pattern, cellular location, activity, regulation, post-translational modifications (PTMs), molecular interactions, three-dimensional (3D)structures and functions of each protein in a biological system. Due to the highly dynamic nature of the proteome, proteomics studies tend to focus on more specific goals as part of approaches to understand the function and regulation of biological systems. Proteome analysis is applied on different levels: (i)to catalogue the proteins synthesized in an organism, tissue or organelle; (ii)to characterize changes occurring during a developmental process; (iii)to identify proteins differing between biological samples or (iv)to identify proteins on the basis of a functional property (e.g. ligand binding). These types of analysis are all illustrated in the different chapters of this book.
Keywords: PLANT PROTEINS; PLANT PROTEOMICS